EFL/ESL Teacher’s Resilience, Academic Buoyancy, Care, and Their Impact on Students’ Engagement: A Theoretical Review - Zhang, Mo (Frontiers in Psychology, 2021)
Teachers’ emotions and inner states play a crucial role in academia as they affect almost all aspects of their job. Language teaching as a stressful and tense profession is full of adversities and traumatic experiences, mandating teachers to be psychologically tough aside from their pedagogical readiness. In tune with this, the current study provides an overview of this area of research drawing on positive psychology and four fresh constructs namely, resilience, buoyancy, care, and students’ engagement. More particularly, this review article presents the definitions, conceptualizations, dimensions, cognate terms, and influential factors related to each construct. Next, related empirical studies are reviewed to justify the results and position the current article in the body of knowledge in this domain. Finally, implications, gaps, and recommendations for future research are presented.